Studying the possibility of confection of hepatitis C and hepatitis G viruses in Iraqi patients (Baghdad Science Journal, 2013)
The aim of this study was spot light to the possibility of confection between hepatitis C&G viruses in Iraqi patients. The groups was studied included two groups as follow:1- first group: its (Infected group) the patients of this group have Anti-HCV abs in their serum by using Indirect ELISA technique.2- second group: its (Control group) the persons of this group have no Anti-HCV abs in their serum by using indirect ELISA technique. The result of this study was observed there was two patients from the first group have Anti-HGVabs in their serum with infection percent 2.70%, also the same result was found in the second group wich mean there was two persons have Anti-HGVabs in their serum with infection percent 8.33% .So when we comparing these groups for obtained the confection between hepatitis Cand G virus the result was showed there was no significant differences between these groups( by using Qi-sequare). Also when we study the effect of sex on HGV infection and prevalence the result was observed that the HGV infection was found in male but not in female and there is high significant differences when we compared the infection percent between diseased group and control group ( by using Qi-sequare). The conclusion of this study there was no confection between HCV&HGV infection or there was a little or limited role in infection, and the sex factor play role in infection..